2016
DOI: 10.1038/ngeo2732
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter losses in German Alps forest soils since the 1970s most likely caused by warming

Abstract: Climate warming is expected to induce soil organic carbon losses in mountain soils that result, in turn, in reduced soil fertility, reduced water storage capacity and positive feedback on climate change. Here we combine two independent sets of measurements of soil organic carbon from forest soils in the German Alps-repeated measurements from 1976 to 2010 and from 1987 to 2011-to show that warming has caused a 14% decline in topsoil organic carbon stocks. The decreases in soil carbon occurred over a period of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 42 publications
10
40
1
Order By: Relevance
“…The numerical approach used here builds on previous work concerning turnover modeling of bomb-radiocarbondominated samples (Herold et al, 2014;Solly et al, 2013;Torn et al, 2009) and the approach used in numerous timeseries analyses with box modeling using Excel (Schrumpf and Kaiser, 2015) or Excel Solver (Baisden et al, 2013;Prior et al, 2007). However, certain modifications were made in order to (i) provide objective repeatable estimates, (ii) incorporate longer time-series data, and (iii) identify samples impacted by petrogenic (also called geogenic) carbon.…”
Section: Modular Robust Numerical Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical approach used here builds on previous work concerning turnover modeling of bomb-radiocarbondominated samples (Herold et al, 2014;Solly et al, 2013;Torn et al, 2009) and the approach used in numerous timeseries analyses with box modeling using Excel (Schrumpf and Kaiser, 2015) or Excel Solver (Baisden et al, 2013;Prior et al, 2007). However, certain modifications were made in order to (i) provide objective repeatable estimates, (ii) incorporate longer time-series data, and (iii) identify samples impacted by petrogenic (also called geogenic) carbon.…”
Section: Modular Robust Numerical Optimizationmentioning
confidence: 99%
“…Given that the so-called "bomb radiocarbon spike" will continue to diminish in the coming decades, time-series measurements are increasingly a matter of urgency in order to take full advantage of this intrinsic tracer (Graven, 2015). Several case studies have collected time-series 14 C soil datasets and demonstrated the value of this approach (Baisden and Parfitt, 2007;Prior et al, 2007;Fröberg et al, 2010;Mills et al, 2013;Schrumpf and Kaiser, 2015). However, these studies are rare, based on single specific sites, and have been rarely linked to abiotic and biotic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…through windfall, the humus is prone to erosion and mineralization (Kohlpaintner & Göttlein, 2009;Mayer, Matthews, Schindlbacher, & Katzensteiner, 2014;Kolb & Kohlpaintner, 2018). Prietzel, Zimmermann, Schubert, and Christophel (2016) showed that since 1970 warming has caused a 14% decline in topsoil organic carbon stocks in the German Alps.…”
Section: Introductionmentioning
confidence: 99%
“…Regional comparisons may introduce unintended artefacts due to the lack of well‐matched resampling observations. Compared to the aforementioned two approaches, repeated soil sampling based on a large number of sites has been suggested to be a solution for realistically detecting the signals of soil C dynamics (Bellamy, Loveland, Bradley, Lark, & Kirk, ; Prietzel, Zimmermann, Schubert, & Christophel, ). However, repeated soil sampling is still lacking across arid/semi‐arid regions.…”
Section: Introductionmentioning
confidence: 99%